Ottoman Judicial Change in the Age of Modernity: A Reappraisal - Rubin, Avi (History compass, 2009)
Legal reform was a key element in the passage of the Ottoman empire to modernity during the ‘long nineteenth century’. This article discusses the modern historiography of Ottoman judicial change while taking issue with the notions of secularization and westernization, which are omnipresent in the conventional legal history of the nineteenth century. An alternative conceptualization is called for, one that is free from the dichotomous and homogenizing binarity of religious/secular, thus allowing more nuanced representations of sociolegal change in general.